Design, synthesis, antibacterial evaluation, and computational studies of hybrid oxothiazolidin–1, 2, 4‐triazole scaffolds. Issue 6 (3rd March 2021) - Pathak, Prateek; Novak, Jurica; Shukla, Parjanya K.; Grishina, Maria; Potemkin, Vladimir; Verma, Amita
Abstract: Bacterial infections are a serious threat to human health due to the development of resistance against the presently used antibiotics. The problem of growing and widespread antibiotic resistance is only getting worse with the shortage of new classes of antibiotics, creating a substantial unmet medical need in the treatment of serious bacterial infections. Therefore, in the present work, we report 18 novel hybrid thiazolidine–1, 2, 4‐triazole derivatives as DNA gyrase inhibitors. The derivatives were synthesized by multistep organic synthesis and characterized by spectroscopic methods ( 1 H and 13 C nuclear magnetic resonance and mass spectroscopy). The derivatives were tested for DNA gyrase inhibition, and the result emphasized that the synthesized derivatives have a tendency to inhibit the function of DNA gyrase. Furthermore, the compounds were also tested for antibacterial activity against three Gram‐positive ( Bacillus subtilis [NCIM 2063], Bacillus cereus [NCIM 2156], Staphylococcus aureus [NCIM 2079]) and two Gram‐negative ( Escherichia coli [NCIM 2065], Proteus vulgaris [NCIM 2027]) bacteria. The derivatives showed a significant‐to‐moderate antibacterial activity with noticeable antibiofilm efficacy. Quantitative structure–activity relationship (QSAR), ADME (absorption, distribution, metabolism, elimination) calculation, molecular docking, radial distribution function, and 2D fingerprinting were also performed to elucidate fundamental structural fragments essential for their bioactivity. These studies suggest that the derivatives 10b and 10n have lead antibacterial properties with significant DNA gyrase inhibitory efficacy, and they can serve as a starting scaffold for the further development of new broad‐spectrum antibacterial agents. Abstract : A series of 18 novel hybrid thiazolidine–1, 2, 4‐triazole derivatives was designed, synthesized, and tested for their activity as DNA gyrase inhibitors as well as their antibacterial activity against three Gram‐positive and two Gram‐negative bacterial strains. Derivatives 10b and 10n show lead antibacterial properties with significant DNA gyrase inhibitory efficacy. They can serve as a starting scaffold for the development of new broad‐spectrum antibacterial agents.